Caracterização molecular do HIV-1 no estado do Ceará : perfil de resistência primária e subtipo - Arruda, Érico Antonio Gomes de (2011)
Prevalence of HIV-1 primary resistance to antiretroviral drugs in Brazil has been variable. In 2001 and 2009 such prevalence was lower than 5% in the Northeast region of the country. The lack of studies on the prevalence of HIV-1 antiretroviral primary resistance in the state of Ceará prompted us to conduct a cross-sectional study of HIV-1 infected patients not yet treated with combined antiretroviral therapy. Blood samples were collected for the genotyping resistance test (TRUEGENE HIV-1 GENOTYPING KIT®) and for the test to identify recent infections (Aware BED EIA HIV-1 Incidence Test®). Sequences were grouped using Stanford University software and statistical analyses were done using the packages Epi-Info 6 and SPSS 16.1. Of 100 patients recruited, 98 included, 24 excluded and 74 sudied from May 2008 through May 2009. The age ranged from 8 months to 67 years old, with 30.6 years of median age. Fifty six patients were males, 77% of them lived in the capital city of Fortaleza or metropolitan region, 86.5% reported sex as the most likely form of acquiring HIV, and the majority of them were men who have sex with men. Of the studied patients, 70.3% were asymptomatic and the median CD4+ count at baseline was 418.5 and 960/mm3 for subjects ≥ 18 and < 18 years old, respectively. Median viral load at baseline was 4.41 and 4.46 log10 for subjects ≥ 18 and < 18 years old, respectively. HIV subtype B was the most prevalent (85.1%), followed by subtype F (8.1%), which was significantly more related with primary resistance (p=0,009), and then subtype C (5.4%). Only 7 cases (6.9%) of recent HIV-1 infections were detected, but in 3 of them the virus was primarily resistant. The prevalence of HIV-1 antiretroviral primary resistance in the state of Ceará in the study period was 9.5%. The identified HIV mutations were 41L, 67N, 215D, 219Q, 101E and 103N in the reverse transcriptase region; and 32I, 46I, 54V, 82T and 90M in the protease region.